Evaluation of compliance with regulatory standards in a clinical analysis laboratory located in the municipality of Castanhal/PA - Batista, João Marcos Braga; Paes, Gleicy Karen Abdon Alves; Pena, Sandro Dias (Brazilian Journal of Production Engineering, 2023)
Work safety is mandatory in clinical analysis laboratories, as well as compliance with the Regulatory Standards (NRs). With a degree of risk 3 (medium), this environment falls within one of the sectors in which most occupational accidents occur in Brazil. The objective of this work is to evaluate compliance with the NRs that are pertinent to the Occupational Health and Safety Management System (OHSMS) in a pathological analysis laboratory. For this, a bibliographical research, on-site visitation and use of a checklist for data collection were carried out. For the analysis and treatment of data, some quality tools were used: Pareto diagram, GUT matrix, checklist and a 5W2H worksheet. The results showed that the company has some non-conformities, the most serious identified are the delay in licenses and the lack of mapping of risks and unhealthy activities. It is understood that the company studied needs an adequate mapping of safety processes; the use of quality tools for the verification of the process of change and control, thus adapting to safety standards and applying the methodology in companies of the same segment. In addition, it will serve as benchmarking for others.
Keywords: Regulatory Norms; clinical analysis laboratory; occupational safety; quality management tools